The Implementation of Facilities and Infrastructure Management in Improving Learning Outcomes in Elementary Schools - Nurjamaludin Nurjamaludin (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
The purpose of this research is to identify 1) how the implementation of facility and infrastructure management at SDN 5 Sindangsari Cimerak is, 2) how the learning outcomes at SDN 5 Sindangsari Cimerak are, 3) what are the supporting and inhibiting factors in the implementation of facility and infrastructure management at SDN 5 Sindangsari Cimerak. This study employs a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation. The obtained data were analyzed using data reduction techniques, data presentation, and conclusion drawing. The results of the study indicate that the implementation of facilities and infrastructure management at SDN 5 Sindangsari Cimerak has been carried out through the stages of planning, procurement, inventory, utilization, maintenance, and disposal. However, challenges remain, such as budget constraints, low awareness of facility maintenance, and inadequate learning facilities. Nevertheless, supporting factors such as assistance from the school administration and the Department of Education contribute to enhancing the effectiveness of facilities and infrastructure management. the improvement in student learning outcomes at SDN 5 Sindangsari Cimerak shows positive results. The main factor supporting the achievement of improved student learning outcomes is teacher competence. Other supporting factors include the management of school facilities and infrastructure, as well as the active role of parents in motivating and monitoring their children's learning activities at home.